Editorial comments - Chris Myburgh (AOSIS, 2008)
The articles in this edition reflect the tradition of well-reasoned research promoted by Health SA Gesondheid. The articles cover a wide scope of demanding issues and range from investigations on the experiences of professional as well as non-professional participants on the provision of health care as a predictor of the turnover rate of professional nurses. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.